(3OhQ eLdS GdOhdI aj MeGjI GdMbhb hGdMQjGJ CKfGA GdXQha GdGSJKfGFjI (B/ s - (3CMeO eMeO Lejd LGO Gddgs; (3LGHQ LGO fUGQs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI(B:s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2023)
(3JJfGhd gPg GdOQGSI, GdHMK aj ehVhY (S0(3OhQ eLdS GdOhdI aj MeGjI GdMbhb hGdMQjGJ GdYGeI CKfGA GdXQha GdGSJKfGFjI(S1 (3adbO efMJ OSGJjQ GdOhd hJTQjYGJgG QFjS GdLeghQjI SdWI JbOjQjI hGSYI aj ehGLgI GdXQha GdESJKfGFjI, aj ebGHd QbGHI bVGFjI, dG SjeG hCf GdXQha GdGSJKfGFjI CUHMJ eSJeQg hJJfGei ckeG hcjkaG(B. (3hJJejR GdQbGHI GdbVGFjI HCfgG GdeXgQ GdYedj GdaYGd dMeGjI GdTQYjI, agi GdJj Jcad JbjjO GdSdWGJ GdYGeI HbhGYO GdbGfhf, ceG Jcad QO gPg GdSdWGJ Edi MOhO GdeTQhYjI Ef gi JLGhRJ Jdc GdMOhO(B. (3hjYO eLdS GdOhdI GdMUf GdPj jdLC Edjg cd ef GfJgcJ Mbhbg Ch bjOJ MQjGJg(B. (3ade Jcf GdEOGQI GdeUQjI JNVY aj CZdH JUQaGJgG ddbGfhf, MJj EfTGA GdeMGce GdeNJdWI YGe (B1875(3e cLgI bVGFjI jNVY dgG CLGfH ge CUMGH GdEeJjGRGJ, hHEfTGA GdeMGce GdCgdjI YGe (B1883(3e, CUHMJ GdefGRYGJ GdEOGQjI JNVY dGNJUGU GdeMGce GdbVGFjI, hbO GSJeQ gPG GdCeQ Edi Cf oCfTF eLdS GdOhdI HGdbGfhf Qbe (B112 (3dSfI (B1946(3e djeGQS GdQbGHI GdbVGFjI Ydi CYeGd GdEOGQI, HOGjI ef QbGHI GdhLhO GdeGOj ddhbGFY , Ke QbGHI GdeTQhYjI, Ke QbGHI GdedGFeI , Ke QbGHI GdehGRfg Hjf GdefGaY hGdCVQGQ aj HYV CMcGeg, djMbb GdVeGfGJ GdJj oJSGge aj MeGjI GdMbhb hGdMQjGJ GdYGeI NGUI aj Xd GdXQha GdGSJKfGFjI, ef NdGd YOI CMcGe haJGhi GfJUQJ aj CZdHgG dMeGjI Mbhb hMQjGJ GdCaQGO GdYGeI hefgG(B: (3GdMQjGJ GdTNUjI hMbhb hMQjGJ GdQCi, hGdMbhb hGdMQjGJ GdSjGSjI, hCNjkQG GdMbhb hGdMQjGJ GdGLJeGYjI hGdGbJUGOjI(B. s
This study deals with research on the topic "The Role of the State Council in Protecting Public Rights and Freedoms During Exceptional Circumstances." State constitutions and legislation have given the President of the Republic wide discretion in the face of exceptional circumstances, in return for judicial oversight, especially since exceptional circumstances have become continuous and growing in quantity and quality.. Judicial oversight is characterized as the practical and effective aspect of protecting legitimacy. It ensures that public authorities are restricted by the rules of law. It also ensures that these authorities are returned to the limits of legality if they exceed those limits. The State Council is the fortress to which anyone whose rights have been violated or their freedoms restricted may resort to. In most of its actions, the Egyptian administration was not subject to the law, until the establishment of the mixed courts in 1875 AD as a judicial authority to which foreigners who are the holders of the privileges were subject. 112 for the year 1946 AD to exercise judicial control over the management's work, starting with the control of the physical existence of the facts, then the control of legality, then the control of appropriateness, then the control of the balance between benefits and harms in some of its provisions, in order to achieve the guarantees that contribute to the protection of public rights and freedoms, especially under exceptional circumstances, Through several rulings and fatwas, most of them were victorious to protect the rights and freedoms of public individuals, including: personal freedoms, rights and freedoms of opinion, political rights and freedoms, and finally social and economic rights and freedoms.
(3CWQhMI (B((3OcJhQGg(B)-(3LGeYI GdbGgQI(B-(3cdjI GdMbhb(B-(3bSe GdbGfhf GdYGe, (B2023s
(3HHdjhLQGajG(B: (3UaMGJ (B603-645.s
(3GdfU HGdYQHjI hGdedNU HGddZI GdEfLdjRjI hGdYQHjI(B.s
Keywords: (3GdbGfhf GdYGes; (3GdMbhb hGdMQjGJ GdYGeIs; (3GdXQha GdGSJKfGFjI s; (3eHOC GdeTQhYjIs; (3GdVeGfGJ GdbVGFjI hGdGLJeGYjIs; (3GdaUd Hjf GdSdWGJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdYGes